In Nagaland... Tapping potential of litchi cultivation - Kumar, Rajesh (Indian Horticulture, 2019)
The physical conditions for litchi production system depends upon geographic location (longitude and latitude), climatic factors (temperature and rainfall) and edaphic (soil) conditions, which are very congenial in Nagaland. The increasing production and productivity of existing litchi plantation through adoption of a balanced mix-hi-tech technology and indigenous technical knowledge, rejuvenation of existing old plantation and area expansion with good quality planting material can bring breakthrough leading to profitability and prosperity in Nagaland.